LANGUAGE LEARNING STRATEGY ADOPTED BY NON-ENGLISH DEPARTMENT STUDENTS IN LEARNING ENGLISH FOR SPECIFIC PURPOSES - Rachmawati, Dwita Laksmita (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
This study investigated on the variation of language learning strategies used by first grade students at ESP (English for Specific Purposes) especially for social and science departments, Merdeka University, Malang. This study used survey study. Both quantitative and qualitative research methods are engaged in this project. Quantitative methods are used to analyze data gathered from questionnaire results, while qualitative data are used to analyze data gathered from one-on-one semi structured interview. The population is 692 first grade students in faculty of economics and business; law, and engineering. The researcher took participant to be the sample of this study randomly in each department with the total participants 70 students. Based on the findings, it can be shown that social class which is represented by faculty of law and faculty of economics and business employ more to the compensation and social language learning strategy while science class which is represented by Faculty of Engineering employ more to the metacognitive strategy.